Pancreatic cancer: failures and hopes—a review of new promising treatment approaches - Vittore Cereda; Mario Rosario D’Andrea (Exploration of Targeted Anti-tumor Therapy)
Pancreatic cancer is a challenging disease with limited treatment options and a high mortality rate. Just few therapy advances have been made in recent years. Tumor microenvironment, immunosuppressive features and mutational status represent important obstacles in the improvement of survival outcomes. Up to now, first-line therapy did achieve a median overall survival of less than 12 months and this discouraging data lead clinicians all over the world to focus their efforts on various fields of investigation: 1) sequential cycling of different systemic therapy in order to overcome mechanisms of resistance; 2) discovery of new predictive bio-markers, in order to target specific patient population; 3) combination treatment, in order to modulate the tumor microenvironment of pancreatic cancer; 4) new modalities of the delivery of drugs in order to pass the physical barrier of desmoplasia and tumor stroma. This review shows future directions of treatment strategies in advanced pancreatic cancer through a deep analysis of these recent macro areas of research.